THEORETICAL PROBLEMS OF THE WORD AND ITS FORMS - Zafar Tillaev Akmalovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
It is natural, considering that interpretation is a human cognitive ability, which allows him to perceive the world not only as a reflection, as non-cue “snapshot”, “photograph”, “cast” of reality, but also to view this reflective information from the point of view of the attitude towards it, including such cognitive properties of a person as his feelings, the ability to assess, determine the pragmatic value. As a consequence of this, the reflected world appears in the form of a conceptual model, in the format a certain conceptual picture of the world, and taking into account the refraction of it in language - as a linguistic picture of the world. According to N.N. Boldyrev, "language a new picture of the world is its definite interpretation and interpreted knowledge about the world in the human mind”